Diagnostic Efficacy of Cell Block and Liquid-Based Cytology for Endoscopic Ultrasound-Guided Fine Needle Aspiration in Pancreatic Tumors - Şenkaya, Ali; Çelik, Ferit; Nart, Deniz; Oruç, Nevin; Aydın, Ahmet (Turkish Journal of Gastroenterology, 2024)
Background/Aims: This study aimed to evaluate the diagnostic efficacy of cell block (CB) and liquid-based cytology (LBC) for endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) in pancreatic tumors. Materials and Methods: The study included patients who underwent EUS-FNA for pancreatic tumors between January 2015 and February 2021 and whose cytology samples were both processed for LBC and CB. Results: Data of 390 patients (220 men, mean age: 64.2 ± 11.4 years) were retrospectively analyzed. Of the detected lesions (size: 17-120 mm; mean: 39.9 ± 13.9 mm), 220 (56.4%) were located in the head and uncinate process of the pancreas. Lesions in 339 (86.9%) patients were diagnosed as malignant using CB and/or LBC and suspicious for malignancy in 44 (11.3%) patients. In 7 patients with non-diagnostic (6 cases) or negative for malignancy (1 case) EUS-FNA results using both methods, the diagnosis of malignancy was established via ultrasound-guided percutaneous biopsy. Malignancy was detected in 324 (92.4%), 313 (87.9%), and 298 (87.9%) patients using CB, LBC, and both CB and LBC, respectively. Final diagnosis was obtained in 339 (98%) patients by using CB and/or LBC. The combined use of the both methods exhibited significantly superior diagnostic accuracy compared with CB and LBC alone (P < .001). Conclusion: Liquid-based cytology and CB exhibit high diagnostic accuracy for the detection of pancreatic tumors in patients undergoing EUS-FNA. The combined use of both methods showed a significantly higher diagnostic accuracy than LBC and CB alone. Cite this article as: Şenkaya A, Çelik F, Tekin F, et al. Diagnostic efficacy of cell block and liquid-based cytology for endoscopic ultrasound-guided fine-needle aspiration in pancreatic tumors. Turk J Gastroenterol. 2024;35(8):665-674.